DETERMINANTS OF THE INTENTION TO PARTICIPATE IN WAQF: ALTRUISM, TRUST, AND RELIGIOSITY - Tegar Rismanuar Nuryitman (Airlangga Journal of Innovation Management, 2022)
This study aims to determine community groups' behavior in participating in waqf. One of the motives that waqf marketers must capture is altruistic behavior in waqf. Altruism is a feeling of wanting to prosper others so that personal interests are sometimes not always important. The feelings of people who always want to help others must be seen and converted into one of the marketing tools in the future. Religiosity is proposed as a moderation of one's altruistic nature in participating in waqf. This study uses the Partial Least Square – Structural Equation Model (PLS-SEM) model, with a total of 61 active waqf in Indonesia. The main finding revealed that altruism significantly affected trust, although it did not affect the intention to participate in waqf. Another significant result reveals that Islamic religiosity moderates the effect of altruism on the intention to participate in waqf if the customer (wakif) has felt trust. In this case, someone with a higher level of religiosity has a greater intention to participate in waqf compared to those with lower religiosity. The significant contribution of this research is the developed theory about the relationship between altruistic attitude, belief, and intention to participate in waqf. This study also recommends practitioners making marketing strategies (segmentation-targeting-positioning) that use customer journeys in altruistic and religious programs. The marketing program is structured in order to find the interest of new wakif candidates as well as to prove credibility so that it will gain trust and in the end will increase a person's intention to participate in waqf.